2017
DOI: 10.1017/s0029665117000052
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the polyphenol and antioxidant activity of different types and forms of millet

Abstract: The demand for functional foods has recently increased, partly due to the growing evidence of several grains and their positive effect on health (1) . Millet is one of such functional grains known for significant health benefits that are attributed to its high content of polyphenols, antioxidants and dietary fibre (2) . Foods such as millet may exert their effect by improving insulin sensitivity and reducing the glycaemic response due in part to a high antioxidant and polyphenol content. Therefore, millet cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Foxtail millet is reported to be relatively tolerant to drought (Lata et al 2010;Karyudi and Fletcher 2003). The nutritious value of this cereal, such as low glycaemic index (Jali et al 2012), high in protein content and rich in dietary fiber (Amadou et al 2013) and containing anti-oxidant (Almaski et al 2017), has made foxtail millet is potentially developed as a functional food. Zhang et al (2012) also reported the potential of this crop as bio-energy source.…”
Section: Introductionmentioning
confidence: 99%
“…Foxtail millet is reported to be relatively tolerant to drought (Lata et al 2010;Karyudi and Fletcher 2003). The nutritious value of this cereal, such as low glycaemic index (Jali et al 2012), high in protein content and rich in dietary fiber (Amadou et al 2013) and containing anti-oxidant (Almaski et al 2017), has made foxtail millet is potentially developed as a functional food. Zhang et al (2012) also reported the potential of this crop as bio-energy source.…”
Section: Introductionmentioning
confidence: 99%
“…The role of non-starch polysaccharides and resistant starch in delaying nutrient digestion and absorption has been extensively reported in a review on health benefits of finger millet (26) Finger millet is also high in polyphenols (8) , which may have a favourable effect on postprandial GR (29) through inhibiting amylase and α-glucosidase enzymes and delaying glucose absorption (26) . Higher polyphenol content has been reported in the grains (30) used to prepare the finger millet muffins, which had twice the amount of polyphenols compared with the wheat muffins in this study. A previous study (31) using cinnamon suggested that insulin receptor stimulation by polyphenols might augment glucose uptake and decrease insulin need, which may partly explain the attenuated IR.…”
Section: Discussionmentioning
confidence: 48%
“…Therefore, novel technology must address the problems with on-field restricted production to find a suitable cereal crop that may serve as an alternative food source and effectively reduce and ease the burden of the significant cereal crops [ 5 , 6 ]. A nutritious and dietary fiber-enriched food alternative concerning important cereal crops is millet [ 7 ]. As a primary cereal crop in the tropical and semiarid regions of Asia, Africa, and the Middle East, millets have a lower vulnerability to adverse weather conditions and a higher yield on marginal land [ [4] , [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…A nutritious and dietary fiber-enriched food alternative concerning important cereal crops is millet [ 7 ]. As a primary cereal crop in the tropical and semiarid regions of Asia, Africa, and the Middle East, millets have a lower vulnerability to adverse weather conditions and a higher yield on marginal land [ [4] , [5] , [6] , [7] , [8] ]. Millets possess excellent amounts of macro and micronutrients, and their importance in the agro-industrial sector is receiving much scientific attention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%